Transition from a two-parent to a single-parent household and child development - Inkyung Kim (Korea Development Institute (KDI), 2021)
As Korea is expected to see an increase in the share of single-parent families, this study analyzes the impact of a family transition from a two-parent to single-parent home on child development. The level of development is measured based on health, self-regulated learning, emotional disorders, selfperception, life satisfaction, peer attachment, school adjustment, sense of community, and multicultural acceptance. According to the analysis, children who have experienced a transition have difficulties in academic time management but see improvements in their attention-deficit/hyperactivity disorders. However, the impact on other development criteria cannot be confirmed. The ability to manage academic time dropped 8.5% while the level of attention and attention-deficit/ hyperactivity disorders improved 14.4%, compared to the averages. These results are possibly due to the fact that the children are able to have a positive relationship with the primary caregiver after the transition as they are no longer caught in the middle of the parental conflict. This finding indicates that contrary to the conventional belief, transitions can also positively influence child development, and thus, policy intervention is needed to alleviate the negative effects on learning ability. Housework support programs should be expanded to enable single parents to spend sufficient time parenting and, if necessary, receive help in better understanding their parental role. Also, schools should lead efforts to improve nurturing and learning environments by serving as a key link between families and local community. Single parents burdened with household chores cannot invest enough time to establish relationships with their children or gain information about nurturing and education. Programs for such services should stretch to reach single parents struggling with labor, study, disease, and disability. Parent education programs that are specifically customized to fit the needs of single parents should be included in housework support programs if needed to resolve grievances in a timely manner. Teachers should serve as a learning coach and emotional support for the children, and counsellor for the parents while closely monitoring the children's learning stages and family conditions that can affect academic performance. To alleviate the academic difficulties of students, schools should encourage teacher cooperation, promote parent-teacher partnerships, and reinforce parents' capability to provide academic support. They should also take the lead in adopting and driving family support services when a child is in need of help that exceeds the capabilities of the school.
Keywords: 330; Alleinerziehende; Kinder; Sozialpsychologie; Sozialer Indikator; Südkorea